Student Responses in using E-Learning Platforms for Biology Subjects Class XI SMA and MA State Semarang City in the Covid-19 Pandemic Era - Anisatuz Zahro'; Afif Amruzain (Bioeducation Journal, 2021)
Biology learning during the Covid-19 pandemic was implemented platfo with the help of an e-learning platform. The variety of e-learning platforms used directly affects the response of students in their use. This research is included in the quantitative research with survey method by using simple descriptive analysis in the form of percentage and presentation of data in tables and diagrams. The purpose of this study was to analyze students' responses to the use of e-learning platforms in biology learning. Sampling in the study uses purposive sampling technique by considering the diversity of e-learning platforms used and the geographical location of the school. The sample taken is students from 5 schools with 3 Upper Secondary Schools (SMA) and 2 Madrasah Aliyah (MA). Data collection techniques through questionnaires. From the results of the study it can be seen that the response of students to the use of e-learning platforms can be said to be positive with an average of 82.93% with 3 schools showing a very positive response, and 2 schools each showing a positive and less positive response. The response shown by students is based on the knowledge and skills of students in technology, especially in terms of the use of e-learning where students who are familiar with technology relatively do not experience many obstacles when faced with online learning.